Eco-cultural identity building through tattoos: a conversational approach - Weder, Franzisca; Burdon, Jasmine; Kearney, Caitlin (Frontiers in Communication, 2023)
While in the not-too-distant past, tattoos were often perceived as representing nonconformity or even deviance, tattoos now increasingly transcend class, gender and age boundaries and are more acceptable than ever. Tattoos are created by artists and an interpretation of a story that the client wants to tell and therefore re-created in interpersonal communication situations -before, during and after the actual tattooing. The project at hand conceptualizes and critically examines the ways in which tattoos alter people's sense of being not only in a semiotic way but also in a conversational way. Our guiding research question is how (much) tattooed images, ornaments, and symbols of nature (re)create the eco-cultural identity of the person wearing it and what role storytelling plays in restoring human-nature relationships.The insights were gained with a series of explorative interviews with (N =) 12 tattoo artists in Oceania (Australia, New Zealand) and Europe (Germany, Austria, France), analysed with an inductive categorization supported by QCAmap (Mayring 2014, Mayring, 2020). The findings show that tattoos are both a device and signifier, and a storytelling method. Bodies are described as landscapes where individual stories were carved out through the process of tattooing and the ritual interactions and conversations tattooed bodies have with others. Tattoos have the potential to re-story the body and shape it in ways that create meaning for the tattooer, the wearer and the society and can create eco-cultural identities and thus regenerate or restore human-nature relationships. This project opens a new field for communication research that helps to strengthen a conversational understanding of communication beyond the ritual perspective. The conceptualization of tattooing as conversational process where meaning is created, common beliefs are (re)produced, new norms are cultivated, and meaningful human-nature relationships are forged stimulates further research studying other rituals and their potential to communicatively re-create a more sustainable society.